Contact notch stress assessment within frictional contact joints (2012)
Stress concentrations at the ends of a flat contact including frictional sliding are analyzed in this article by using the finite element (FE) method. The numerical studies are conducted with a shaft coupled to the hub by conical rings. The applied mesh refinement at the contact ends assures the reliability of the FE results, which show significantly higher stress peaks than those obtained from the conventional analytical solution recommended in the design guidelines of the frictional conical joints. These notch stresses result in low cycle fatigue (LCF) failures of the shaft-hub connection in service, since the yield point of the shaft material can be locally exceeded. The effect of clearances among the joint components and magnitudes of the friction coefficient on variations of the maximum stress in the contact are considered as well. The paper's findings and conclusions are applicable to the design and manufacturing process of the frictional conical joints with regard to assembly tolerances.